2002
DOI: 10.1093/aje/155.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Estrogen Exposure and Cardiovascular Mortality Risk in Postmenopausal Women

Abstract: In this study, the authors investigated whether combined information on reproductive factors has additive value to the single reproductive factor age at menopause for assessing endogenous estrogen exposure and cardiovascular mortality risk in postmenopausal women. They conducted a population-based cohort study that included 9,450 postmenopausal women from Nijmegen, the Netherlands, who were aged 35--65 years at enrollment in 1975, with a median follow-up of 20.5 years. A Cox proportional hazards model and Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 28 publications
5
112
1
1
Order By: Relevance
“…To date, epidemiological studies have reported that AAM could predict CVD [4][5][6][7] ; however, there is no uniform definition of the AAM cutoff point, and the…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, epidemiological studies have reported that AAM could predict CVD [4][5][6][7] ; however, there is no uniform definition of the AAM cutoff point, and the…”
Section: Resultsmentioning
confidence: 99%
“…Women with early menopause have elevated CVD 4,5) , and late menopause has shown reduced CVD 6,7) ; however, the independent influence of natural AAM on CRF remains unclear.…”
Section: Natural Menopause Status and Age At Menopausementioning
confidence: 99%
“…Consequently, hormone therapy use may confound the relationship between age at menopause and CVD risk. Indeed, HRT was only adjusted for in a minority of identified studies [27][28][29][30][31] . Moreover, since the number of available studies in some of our analysis was small, it precluded our ability to comprehensively assess the impact of type of menopause in our results.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Many epidemiologic studies indicated that an early natural menopause increased the risk of ischemic heart disease. [1][2][3][4] Furthermore, a vast amount of observational studies suggested that hormone replacement therapy (HRT) protected postmenopausal women from cardiovascular disease. 5 Many basic studies also suggested that estrogen had protective effects on the cardiovascular system.…”
mentioning
confidence: 99%